Analisis Indeks Keanekaragaman, Keragaman, dan Dominansi Ikan di Sungai Aur Lemau Kabupaten Bengkulu Tengah - Intan Febrian; Euis Nursaadah; Bhakti Karyadi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Fish is one of the biological natural resources that has high diversity in river ecosystems. The purpose of this study was to determine the diversity index, diversity index, and fish dominance index in the Aur Lemau Watershed, which is located in Pondok Kelapa District, Central Bengkulu Regency. This type of research is descriptive quantitative. This research was conducted in January-August 2021. The sampling method used was purposive random sampling. Determination of the sampling location is recommended in the relatively different environmental conditions and fishing areas that are usually carried out by the surrounding community. This study found as many as 14 species of fish with a total number of 146 fish. The order that dominates the fish in the waters of the Aur Lemau River is the order Perciformes with a total of 8 families and 8 species. Based on the results of the calculation of the diversity index value of station I is 2.09; station II of 1.9; and station III of 1.3. Then, the uniformity index value of station I (0.96); station II (0.92); and station III (0.81). The highest dominance index is at station III with a value of 0.31. The dominance index value of station I is 0.14 and station II is 0.12.